Soil rehabilitation following tractor logging: early results on amendments and tilling in a second rotation Acacia mangium plantation in Sabah, Malaysia - Ilstedt, Ulrik (2004)
Timber extraction with crawler tractors in humid tropical forests causes degradation of soil physical properties and decreases plant growth. We tested rehabilitation of tracks in a second rotation Acacia mangium plantation in Sabah, Malaysia, by tilling with additions of NPK-fertilizer, ash and organic material to a depth of 15–20 cm. Two years after planting total basal area of A. mangium seedlings was 62% higher outside tracks compared to unimproved tracks, while on NPK-fertilized tracks performance was 700% higher compared to unimproved tracks. Corresponding figures for average height were 40 and 80%. After 8 days with little rain track topsoil experienced water shortage with all studied soil improvements. For ‘non-tracked’ areas wilting-point (-1500 kPa) was not reached during 17 days of dry weather, and more meso-pores were present. Consequently, depending on rainfall after planting the effect of soil rehabilitation on tree performance may be less positive than shown here, because dry periods of 2 weeks length are common in the humid tropics. Bulk density on plots outside tracks in this second-generation plantation was 60% higher than have been reported in similar first generation plantations. It is discussed that this might be a warning that repeated logging and fire may have a detrimental effect on soil physical properties.